HIV testing algorithm using fourth generation reagents reduces the false positive rate of screening tests - Gou, Yu; Gao, Zhengxiang; Duan, Yifei; Wu, Yu; Peng, Leiwen (Scientific reports, 2025)
To analyze the false-positive results of HIV screening in a women’s and children’s specialized hospital and discuss the improved effect of the testing algorithm that retesting with two fourth-generation HIV assays to reduce false-positive results. We retrospectively analyzed 380,390 samples tested with Roche Elecsys ® HIV combi PT assay from 2020 to 2023. The responsive samples were retested using the Determine HIV Early Detect assay (Abbott Diagnostic) and the Elecsys ® HIV DUO assay (Roche Diagnostic). Finally, the supplemental tests were used to confirm whether the sample is true positive. Of the 380,390 samples, 555 were reactive with Roche Elecsys ® HIV combi PT assay. After re-testing with the Determine HIV Early Detect assay and Elecsys ® HIV DUO assay, the reactive sample was reduced to 256 cases, and finally 122 cases were confirmed as true positive by supplementary tests. The false positive rate was reduced from 0.11 to 0.04%. The median cut-off index (COI) of false positive samples was significantly lower than that of true positive samples. Pregnancy, tumor and infertility are the top three clinical diagnoses of false positive patients (19.92%, 15.23% and 13.67%, respectively). Retested with two different fourth-generation HIV assays can significantly reduce the false positive rate and improve the positive predictive value. False-positive samples still require longer follow-up to rule out HIV infection.